m6A reader IGF2BP2-stabilized lncRNA LHX1-DT inhibits renal cell carcinoma (RCC) cell proliferation and invasion by sponging miR-590-5p - Chunming Zhu; Ruiming Li; Xiangyun You; Jie Xu; Jiahe Wang; Dan Dong; Xiaonan Chen; Kefeng Wang (npj Precision Oncology)
Abstract N6-methyladenosine (m6A) has been established as a critical regulator in various human cancers. However, the role of m6A modification in renal cell carcinoma (RCC) and its interaction with long non-coding RNA LHX1-DT (LHX1-DT) remains unclear. Differentially expressed lncRNAs and m6A levels were identified through microarray analysis. The interaction between IGF2BP2 and LHX1-DT was examined via RNA immunoprecipitation and luciferase reporter assays. LHX1-DT expression was found to be downregulated in RCC tissues, and reduced expression of LHX1-DT was associated with poor overall survival in RCC patients. Functional assays demonstrated that overexpression of LHX1-DT significantly inhibited RCC cell proliferation and invasion. The m6A reader protein IGF2BP2, mediated by METTL14, recognized the m6A modification site on LHX1-DT and promoted its stability. Additionally, LHX1-DT acted as a competing endogenous RNA (ceRNA) by sponging miR-590-5p, which in turn downregulated PDCD4, thereby inhibiting RCC cell proliferation and invasion. LHX1-DT serves as an independent prognostic biomarker for RCC, and the IGF2BP2/LHX1-DT/miR-590-5p/PDCD4 axis represents a novel therapeutic target for RCC progression.